UJI TOKSISITAS AKUT EKSTRAK ETANOL BUAH LAKUM (Cayratia tryfolia) TERHADAP LARVA Artemia salina Leach DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Retno Prasetya; Iis Intan W (PROSIDING SEMINAR KIMIA, 2013)
Lakum fruit use as spices could be hint for one of traditional herbal plant which using Brine Shrimp Lethality Test (BSLT) method in toxicity test. From the method, it will be know acute toxicity potential on lakum fruit’s extract against Artemia salina Leach larvae. This research was an experimental research using Post Test Only Control Group Design. It is used 160 larvaes as test animal which is divided on 4 groups, each group is done by the replication of research for 3 times and one control for each group. The various of concentration is 200 ppm, 400 ppm, 800 ppm, and 1600 ppm. The result is against larvae that died 24 hours after component test was given. Through the data, LC 50 value of ethanol extract of lakum fruit was analyzed by linear regression. Bassed on the researched, the value of LC 50 of ethanol extract of lakum fruit is172.38 μg/ml. The value of LC 50 is less than 1000 ppm. It’s mean that the extract had acute toxicity potential against Artemia salina Leach larvae.